Immediate Postoperative Complications and Recovery Profile Following Spinal Anaesthesia: A Comparison Between Pethidine and Bupivacaine - Sabeen Arjumand, Fareeha, Hajra Tariq, Wajiha Zahid, Zoobia Irum, Shahnaz Fatima, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Spinal anaesthesia is a less expensive option to general anaesthesia for surgical procedures below the umbilicus in resource-constrained settings with a shortage of medical gases and specialized an anesthetists. The patient’s airway is not harmed by spinal anaesthesia, and both the patient and the doctor benefits from a host of additional benefits. Following the discontinuation of hyperbaric lidocaine for intrathecal injection because it can results in radiculopathy, bupivacaine is frequently used for spinal anaesthesia. For spinal, doctors employ pethidine, a lipophilic opioid with local aesthetic properties. In this study, pethidine bupivacaine were used as the only anaesthetic a gents to perform spinal anaesthesia, and the immediate postoperative problems and recovery profile were compared. Methodology: For quick surgical procedures on the lower body, 52 American Society of Anesthesiologists physical status I and II patients between the ages of 18 and 60 were randomly assigned to receive spinalanaesthesia. The patients' recovery times for pinprick sensation at S2, plantar flexion, big toe proprioception, and full motor recovery (Bromage score 0) were compared after receiving either 2.5mL of isobaric 0.5 percent bupivacaine or 1mg/Kg of preservative-free pethidine. The immediate postoperative period complications of pain, drowsiness, nausea and vomiting, pruritus, and urine retention were compared. Results: The time to return of pinkprick sensation at S2 was 94.6220.25 minutes and 205.9631.05 minutes, respectively, when pethidine and bupivacaine were compared. Pethidine and bupivacaine had a time to return of plantar flexion of 92.8812.01 minutes and viii 1 93.8539.56 minutes, respectively. Between pedthidine and bupivacaine, the mean recovery times f or the big toe’s proprioception were 31.159.41 and 172.5042.70 minutes, respectively, for full motor recovery (Bromage score 0). All recovery time variation were significant (p 0.0001) across the broad. There was no discernible change in the incidence of pain or sedation in the immediate postoperative period. In the Bupivacaine group, four patients (15. 38%) reported having hardly bearable discomfort. Both groups did not experience any instances of nausea or vomiting. Pruritus was experience by five patients (19.22%) in the pethidine group, but none in the bupivacaine group (0.00 %). Urinary retention incidence varied, and this difference was significant (p = 0.048) Conclusion: Compared to bupivacaine, pethidine had a quicker recovery profile and didn't lead to any major complications right after surgery.